Novel antimicrobial ointment for infected wound healing in an in vitro and in vivo porcine model. Issue 5 (6th May 2021) - Hachem, Ray; Parikh, Umang M.; Reitzel, Ruth; Rosenblatt, Joel; Kaul, Aditya; Vargas‐Cruz, Nylev; Hill, Lori; Moore, Lisa; Meyer, Jennifer; Chaftari, Anne‐Marie; Gagea, Mihai; Balaji, Swathi; et al.
Abstract: Microbial contamination of wounds is a significant problem that delays healing, particularly when bacterial biofilms are present. A novel combination of pectinic acid (PG) + caprylic acid (CAP) was previously found in vitro to be highly effective in eradicating various pathogens in biofilms with minimal cytotoxicity. In this study, a novel wound ointment was formulated with PG + CAP and first assessed in vitro using a well‐established biofilm eradication model. In vitro, the PG + CAP ointment was shown to be efficacious in reducing the microbial biofilms. This ointment was then tested in vivo in two pilot porcine wound healing models, with and without Staphylococcus aureus microbial challenge. Ointments were applied to each wound daily, and healing by wound closure area measurement was assessed weekly over 4 weeks. After 4 weeks, pigs were sacrificed and wounds were scored for reepithelialization, inflammation, granulation tissue, and collagen deposition. We compared PG + CAP to hydroxyethylcellulose + glycerol ointment base (control) and MediHoney (comparator). In the porcine microbial challenge model, the novel antimicrobial PG + CAP wound ointment rapidly eradicated bacterial organisms embedded in wounds, was safe and well‐tolerated, and was associated with enhanced healing compared to ointment base and MediHoney. Specifically, the cumulative histopathology, reepithelialization of epidermis, and mature granulation tissue in the wound bed was significantly better with PG + CAP than with control and MediHoney treatments. This ointment warrants further study as a non‐antibiotic ointment for use in treating a wide array of infected wounds.